Migration crisis versus the control of the borderlines within the European Union - Marcinkowski, Tomasz (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2019)
Freedom of movement is one of the basic achievements and effects of the European integration process. Benefiting from this freedom has become an important experience for millions of the Europeans. Crisis phenomena, mainly related to the migration breakdown, revealed institutional and legal problems and had an impact on public opinion. The sense of threat and political and organizational difficulties led to the decision to reinstate control on the internal borders in many places in the EU. As it appears from nationwide surveys, there is also acceptance in Poland of such activities. Research conducted on the Polish-German borderland indicates that also the inhabitants of these areas support such decisions, but the degree of acceptance of the restoration of border control is lower here than in national surveys.

Swoboda przemieszczania się jest jednym z podstawowych osiągnięć oraz efektów procesu integracji europejskiej. Korzystanie z tej wolności stało się ważnym doświadczeniem milionów Europejczyków. Zjawiska kryzysowe, związane przede wszystkim z kryzysem migracyjnym ukazały problemy instytucjonalno-prawne oraz miały wpływ na opinię publiczną. Poczucie zagrożenia i trudności polityczne i organizacyjne doprowadziły do decyzji o przywróceniu kontroli na wewnętrznych granicach w wielu miejscach UE. Jak wynika z badań ogólnopolskich, także w naszym kraju jest akceptacja takich działań. Badania przeprowadzone na pograniczu polsko-niemieckim wskazują, że także mieszkańcy tych terenów popierają takie decyzje, jednak stopień akceptacji przywracania kontroli granicznych jest tu mniejszy niż w badaniach ogólnopolskich.
Kryzys migracyjny a kontrola granic wewnątrz Unii Europejskiej
Keywords: migration crisis; border control; European integration; Schengen; security; kryzys migracyjny; kontrola graniczna; integracja europejska; Schengen; bezpieczeństwo